Application of Aromatherapy and Yoga to Mitigate Weight Gain Side Effects Among Injectable Contraceptive Users at Kasih Ibu Clinic (JURNAL PENGMAS KESTRA (JPK), 2025)
This Community Service Program (PKM) aims to address weight gain in injectable contraceptive acceptors through the approach of aromayoga. The program involved 30 participants who experienced weight gain due to the use of the three-month injectable hormonal contraception. The program began with weight measurements and a pre-test to assess participants' knowledge about aromayoga. Participants were then provided with education on the benefits of aromayoga as a non-pharmacological solution for managing weight, including basic concepts of aromayoga, its health benefits, and how to apply it in daily life. After the education session, a demonstration and hands-on practice were conducted where participants practiced breathing techniques, yoga poses, and aromatherapy application. At the end of the program, participants took a post-test to evaluate changes in their knowledge, while their weight was measured again to assess physical changes. The evaluation results showed a significant improvement in participants' knowledge, with the average score increasing from 57.1 in the pre-test to 86.7 in the post-test, marking an average increase of 51.9%. The largest increase was observed in the "Techniques and procedures for applying aromayoga according to SOP" indicator, which rose by 76.0%. Additionally, participants' skills also showed improvement, with 70% demonstrating excellent skills in practicing aromayoga techniques. This program successfully provided knowledge and skills that can be applied in daily life to manage weight gain caused by injectable contraceptives.